Pedagogical and Psyhological Basis of Moral Education - Barakoska, Aneta; Aneta Jovkovska (IJCRSEE, 2013)
Analyses of pedagogical and psychological literature show that education and upbringing are oriented to nursing moral values. In pedagogy’s historical context, the most important goals are education, development, and selfdevelopment of life experience and student’s perception of efforts to build values in their own life. In different historical periods, different moral values appear in the society. They are united by being directed towards humanism and on the basis of personal experience they represent completeness of general principles and norms of student’s behavior towards other people, nature, society and towards student’s themselves in the name of the common good. The already formed moral values have regulatory function in student’s life. The research problem is connected with humanization of the educational process.
(IJCRSEE) International Journal of Cognitive Research in science, engineering and education. Vol. 1, Issue.2
Keywords: moral, development, values, upbringing, behavior, orientations, student, religion, society